Comparison of the Level of Knowledge of Housewives and Working Mothers on the Development of 5-6 Year Old Children with KPSP Planning - Umu Kalsum; Hasriani Hasriani; Suherman Suherman; Astuti Astuti (LPPM STIKes Muhammadiyah Ciamis, 2023)
Children aged 5–6 years are at preschool age; this period is also said to be the golden period and window of opportunity because children are starting to enter a new, unfamiliar environment and learn many new things. During this period, mothers play an important role in providing early stimulation for children's development, so the mother's knowledge and attitudes are very influential. The aim of this research was to determine the comparison of knowledge between housewife mothers and working mothers regarding the development of children aged 5–6 years using the KPSP assessment at Pembina Matakali Kindergarten. The type of research used in this research is a correlation study, and the research design used is analytical with a cross-sectional approach. The population in this study consisted of 38 mothers and children aged 5–6 years at the Pembina Matakali Kindergarten and a sample of 38 mothers and children aged 5–6 years at the Pembina Matakali Kindergarten using total sampling. The results of the Chi Square Test obtained an asymp.Sig (2-Sided) Continuity Correlations value of 0.00 (0.00<0.05), so it can be concluded that Ho is rejected and Ha is accepted, which means that there is a significant relationship between the knowledge of the housewife and mother works on the development of children aged 5–6 years with KPSP research at Pembina Matakali Kindergarten. It is hoped that suggestions from this research can provide information to mothers about the importance of a mother's role in the child's development process.